Usefulness of serum S100A4 and positron‐emission tomography on lung cancer accompanied by interstitial pneumonia. Issue 4 (19th December 2022) - Kagimoto, Atsushi; Tsutani, Yasuhiro; Kushitani, Kei; Kambara, Takahiro; Mimae, Takahiro; Miyata, Yoshihiro; Takeshima, Yukio; Okada, Morihito
Abstract: Background: The S100 calcium‐binding protein A4 (S100A4) and the accumulation of [18F]‐fluoro‐2‐deoxy‐D‐glucose (FDG) in noncancerous interstitial pneumonia (IP) area are predictors of postoperative acute exacerbation (AE) of IP after pulmonary resection for lung cancer with IP. However, the significance of combining these markers for predicting short‐term outcome and long‐term prognosis is not known. Methods: Patients diagnosed with IP on preoperative high‐resolution computed tomography and who had undergone pulmonary resection for primary lung cancer between April 2010 and March 2019 at Hiroshima University were included in this study. Predictive factors for the cumulative incidence of death from other than lung cancer (CIDOL) were investigated using the Fine and Gray model. CIDOL, perioperative outcome, and cumulative incidence of all death (CIAD) were retrospectively compared based on serum S100A4 and FDG accumulation. Results: A total of 121 patients were included in this study. High S100A4 (hazard ratio [HR], 2.541; p = 0.006) and FDG accumulation (HR, 3.199; p = 0.038) were significant predictors of CIDOL. AE of IP occurred only in patients with high S100A4/FDG (+). CIDOL of patients with high S100A4/FDG (+) was higher than those with high S100A4/FDG (−) or low S100A4/FDG (+) ( p < 0.001), and CIAD of patients with high S100A4/FDG (+) was also higher than those with high S100A4/FDG (−) or low S100A4/FDG (+) patients ( p = 0.021). Conclusions: Serum S100A4 and FDG accumulation in the noncancerous IP area were significant predictors of CIDOL after lung resection for lung cancer with IP and may help decide the treatment strategy. Abstract : We investigated the significance of serum S100A4 and FDG accumulation in predicting prognosis after lung resection for lung cancer with interstitial pneumonia. S100A4 and FDG accumulation were significant predictors of cumulative incidence of death from other than lung cancer (CIDOL) in multivariable analysis. CIDOL was significantly higher in patients with high S100A4/FDG (+).